Soil moisture and its importance for tundra plants - Kemppinen, Julia (Department of Geosciences and Geography, ISSN 1798-7911, 2020)
Abstract in Finnish.
Keywords: arktinen alue; maaperä; kosteus; vesi; kasvit; vuorovaikutus; ekosysteemit (ekologia); tundra; kasvillisuus; putkilokasvit; sammalet; jäkälät; puuvartiset kasvit; tunturit; tunturipaljakka; Fennoskandia